2006
DOI: 10.1562/2005-11-23-ra-739
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Human Serum Albumin on Photodegradation of Folic Acid in Solution

Abstract: It has been proposed that photodegradation of folates may be the reason for the pigmentation of races living under high fluence rates of ultraviolet radiation. The photodegradation of folic acid (FA) induced by ultraviolet-A (UV-A) radiation, in solution and in the presence of human serum albumin (HSA), was studied with absorption and fluorescence spectroscopy. FA photodegradation, with formation of p-aminobenzoyl-l-glutamic acid, 6-formylpterin and pterin-6-carboxylic acid, was found to follow an exponential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 24 publications
(47 reference statements)
2
31
0
Order By: Relevance
“…Some investigators 6,7,19) have already shown that PGA was degraded by UVA exposure, however, these experiments just showed the detection of the degraded compounds. No quantitative experiment had been reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some investigators 6,7,19) have already shown that PGA was degraded by UVA exposure, however, these experiments just showed the detection of the degraded compounds. No quantitative experiment had been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The main folate supplement that is available on the market is PGA, which is a synthetic form of folate, and is the oxidized and most stable form of folates. However, the demerit of PGA is that it is destroyed by UVA exposure 6) which partly penetrates into the blood stream. Therefore, there is the possibility of a reduction of the blood folate level with sunlight exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of its pharmacological activity, the investigation of the interactions between this compound and biomolecules are very important [13]. Furthermore, binding of drugs to albumin alters the pattern and volume of distribution, lowers the rate of clearance, and increases the plasma half-life of the drug [12][13][14][15].…”
Section: Ciprofloxacinmentioning
confidence: 99%
“…It is a globular, multifunctional protein composed of three structurally similar domains each containing two subdomains and having molecular weight of 67 kD stabilized by 17 disulfide bonds [13]. Apart from ligands binding and transport, it involves in maintaining pH and osmotic pressure, preventing photodegradation of folic acid, and is also a marker of inflammatory state [14,15].…”
Section: Introductionmentioning
confidence: 99%